Morphological abnormalities in natural populations of the common South American toad Rhinella arenarum inhabiting fluoride-rich environments - Pollo, Favio Ezequiel (2019)
Morphological abnormalities in amphibians may be attributed to contaminants, ultraviolet radiation and trematode parasites, or a synergistic effect between them. In the present study, morphological abnormalities in Rhinella arenarum adults from natural and artificial fluoride-rich environments were identified and evaluated. Three sites were sampled in central Argentina: Los Vallecitos stream (LF-LV), Los Cerros Negros stream (MF-CN), and Decantation ponds (HF-DP), with low (0.33 mg/L), middle (2.03 mg/L) and high (14.0 mg/L) fluoride levels respectively; the latter site is associated with a fluoride mine. Abnormal individuals were photographed and then standard radiographs were taken. Abnormality frequencies and relative percentage of abnormal individuals were calculated for each site. In addition, skeletochronology was used to estimate toad's age. Five abnormality types were identified: syndactyly, ectrodactyly, polydactyly, microphthalmia and ectromelia. Percentages of abnormal individuals per site were: LF-LV = 4%, MF-CN = 21.2% and HF-DP = 6.4%. The MF-CN and HF-DP populations had morphological abnormality frequencies that exceeded the reference value (5%) reported in the literature. The average age did not differ between sites. The results of this study indicate that there is an association between frequency of morphological abnormalities and high fluoride levels.